The Influence of Original Regional Income, Capital Expenditures, and General Allocation Funds on the Financial Performance of the Regional Government of Brebes Regency for the 2022-2023 Fiscal Year - Anggih Anggih; Roni Roni; Yenny Ernitawati (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to find out the influence of PAD, Capital Expenditures and DAU on the financial performance of the regional government of Brebes Regency in 2022-2023. Quantitative descriptive research used in this research with secondary data used and obtained from the Brebes Regency BPKAD office. This research uses descriptive analysis, classical test, multiple linear, t hypothesis test, f test, and coefficient of determination test using SPSS 22 features. In this research the results show that PAD has a positive and significant effect on local government financial performance, then capital expenditure has a positive effect but it is not significant for regional government financial performance, and for DAU it has no effect on regional financial performance. It can be concluded that PAD and capital expenditure influence regional government financial performance, but not general allocation funds which do not influence regional government financial performance.